2018
DOI: 10.1088/1361-6668/aaee05
|View full text |Cite
|
Sign up to set email alerts
|

An effective way to reduce AC loss of second-generation high temperature superconductors

Abstract: Second-generation (2G) high temperature superconducting (HTS) devices have high power density and efficiency for energy applications. However, in alternative current conditions, the vortex movement in 2G HTS leads to energy dissipation at low temperatures, which significantly affects efficiency and adds an extra burden to cooling systems. This energy dissipation is identified as AC loss. Reducing AC loss to improve efficiencies of 2G HTS devices, e.g. HTS machines, cables and fault current limiters, has become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The results have demonstrated that the critical current is not debased for striation width over 150 µm, and the AC loss can be decreased effectively. Different from conventional filamentary HTS CCs, a soldered-stacked-square (3S) wire has been proposed in [216]. The fundamental manufacturing process is to divide HTS CCs into 1-mm-wide ones, solder with a soldering furnace, and put them into a stack, as shown in Figure 15.…”
Section: Ac Loss Reduction Techniques 61 Filamentation Of Hts Ccsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have demonstrated that the critical current is not debased for striation width over 150 µm, and the AC loss can be decreased effectively. Different from conventional filamentary HTS CCs, a soldered-stacked-square (3S) wire has been proposed in [216]. The fundamental manufacturing process is to divide HTS CCs into 1-mm-wide ones, solder with a soldering furnace, and put them into a stack, as shown in Figure 15.…”
Section: Ac Loss Reduction Techniques 61 Filamentation Of Hts Ccsmentioning
confidence: 99%
“…The fundamental manufacturing process is to divide HTS CCs into 1-mm-wide ones, solder with a soldering furnace, and put them into a stack, as shown in Figure 15. In [216], the authors reported that the 3S concept can help to decrease AC loss by 80% compared with originally uncut tapes.…”
Section: Ac Loss Reduction Techniques 61 Filamentation Of Hts Ccsmentioning
confidence: 99%
“…Basic mechanical and transport characteristics of the REBCO conductor after narrowed and stacked have been studied in our previous work [19][20][21]. Specially, when the bending diameter is larger than 60 mm, the critical current of the stacked REBCO conductor will not be reduced.…”
Section: Fabrication Of Ns Wire and Coilmentioning
confidence: 99%
“…The theories of magnetization loss in thin superconducting strips developed by Brandt et al [108] and Zeldov et al [142] indicate that the magnetization loss is proportional to the HTS tapes' width at the same Ic. Therefore, an effectively method to reduce AC loss in REBCO conductor is cutting a single tape into multi narrow filaments [25]- [27].…”
Section: Striated Wiresmentioning
confidence: 99%
“…In a striated REBCO wire, the superconducting layer is striated into separated narrow filaments. As a consequence, the magnetization loss can be significantly reduced due to the decreased size of the induced current loops [25]- [27]. A Roebel REBCO cable consists of several conductor strands.…”
mentioning
confidence: 99%